Pengaruh Green Marketing Mix Terhadap Green Product Purchase Intention Pada Produk Innisfree Di Jakarta Dengan Consumer’s Attitude Sebagai Variabel Mediasi - Stevany Febriani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aimed to know the responses of the people about green marketing towards green product purchase intention on Innisfree products with consumer’s attitude towards green product as the mediating variable. The variables used were green product, green price, green place, green promotion, green product purchase intention and consumer’s attitude. This study uses quantitative method. The data collection technique use questionnaires distributed to 400 respondents namely Innisfree consumers in Jakarta with purposive sampling method. The analysis method that used in this study was path analysis. The result showed that green marketing mix positively and significantly affect to consumer’s attitude and consumer’s attitude positively and significantly affect green product purchase intention. The partial green product and green price x positively and significantly affect the green product purchase intention, green place and green promotion no significant effect to green product purchase intention. Consumer’s attitude positively and significantly affect the green product purchase intention on Innisfree product. Consumer’s attitude is fully mediated the green place and green promotion affect on green product purchase intention and partial mediated the green product and green price affect on green product purchase intention.